If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 7 = 82 Reorder the terms: 7 + 3n = 82 Solving 7 + 3n = 82 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3n = 82 + -7 Combine like terms: 7 + -7 = 0 0 + 3n = 82 + -7 3n = 82 + -7 Combine like terms: 82 + -7 = 75 3n = 75 Divide each side by '3'. n = 25 Simplifying n = 25
| 16=10-(4x+2) | | 5.34086e=231 | | -16t^2+80t+4=h(t) | | 4x=12+3x-x | | 1/2(6x-1/3) | | 72=-8m-24 | | 3x-43=2x-13 | | y-7=8(x-6) | | 3(x+5)=ex | | 2x+1=1-3x | | y+9=-5(x+6) | | 12x^2-26=x | | 72=-84-24 | | 0.3x^2-x=0 | | 7x-9*3=5x-6 | | y+10=7(x-9) | | -8+49r^2=-4 | | 8y-12=4y+8 | | y=85+10x | | -7=1-2b-2b | | 2(x+4)=5+2x | | 44=-7f-5 | | (4x+2)+(3x+19)=180 | | 4b-8=10-3b | | 0.33x^2-x=0 | | 10n+98=-872 | | 3=1/x | | -7(-1+5v)-5v=-39+6v | | 4(2y-5)+5y=7 | | 5x+4=8x-12 | | 6x-12-2x=5x-2 | | -4=-4r+32 |